2017
DOI: 10.1159/000479999
|View full text |Cite
|
Sign up to set email alerts
|

PPARα Agonist Stimulated Angiogenesis by Improving Endothelial Precursor Cell Function Via a NLRP3 Inflammasome Pathway

Abstract: Background: Impaired wound healing is a common complication of diabetes and is the leading cause of lower extremity amputation. Treatment with fenofibrate, a peroxisome proliferators–activated receptor α (PPARα) agonist, was associated with a lower risk of amputations, particularly minor amputations without known large-vessel diseases, probably through non-lipid mechanisms. The current study aimed to test our hypothesis that fenofibrate stimulates angiogenesis and restores endothelial precursor cell (EPC) func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 44 publications
2
33
0
1
Order By: Relevance
“…In endothelial cells, the NLRP3 inflammasome exhibits a significant initiating mechanism, and its activation may accelerate the development of endothelial dysfunction or atherogenic pathology by inducing plasma trimethylamine-Noxide (TMAO) [38]. The repression of the NLRP3 inflammasome is a critical factor in I/R or inflammation by correlation with SIRT1, which was proved to be involved in both preventing cells from injury induced by various stress and improving endothelial precursor cell function [39,40]. Activating the NLRP3 inflammasome signaling can promote atherosclerosis pathogenesis via the overexpression of inducible endothelial-specific GPR124 [41].…”
Section: Discussionmentioning
confidence: 99%
“…In endothelial cells, the NLRP3 inflammasome exhibits a significant initiating mechanism, and its activation may accelerate the development of endothelial dysfunction or atherogenic pathology by inducing plasma trimethylamine-Noxide (TMAO) [38]. The repression of the NLRP3 inflammasome is a critical factor in I/R or inflammation by correlation with SIRT1, which was proved to be involved in both preventing cells from injury induced by various stress and improving endothelial precursor cell function [39,40]. Activating the NLRP3 inflammasome signaling can promote atherosclerosis pathogenesis via the overexpression of inducible endothelial-specific GPR124 [41].…”
Section: Discussionmentioning
confidence: 99%
“…Fenofibrate is a selective agonist of peroxisome proliferator-activated receptor α (PPARα) that prevents the progression of microvascular complications in T2DM. Deng et al found that fenofibrate promotes wound healing via alleviating EPC dysfunction and stimulating angiogenesis in diabetic mice induced by streptozotocin (STZ), the effects of which are attributed to the inhibition of NLRP3 inflammasome pathway 101 .…”
Section: Hypoglycemic Agentsmentioning
confidence: 99%
“…For example, fibrates, which are PPARα ligands, are used widely to ameliorate the microvascular risks associated with metabolic syndrome [26]. This class of exogenous PPARα ligands includes clofibrate, gemfibrozil, fenofibrate, bezafibrate, and ciprofibrate [27][28][29][30][31][32]. Furthermore, the synthetic compounds GW501516, GW0742, L-165041, and GW2433 have been defined as selective PPARβ/δ ligands [33,34].…”
Section: General Characteristics and Roles Of Pparα Pparγ And Pparβ/δmentioning
confidence: 99%